Peningkatan Literasi Kesehatan Mental Santri di Pondok Pesantren Sirojul Ulum As-Sarqowi Malang - Muhammad Hilal; Abdul Wahid Purnama (Jurnal Aksi Afirmasi, 2026)
Adolescent mental health is a crucial aspect of academic success, yet attention to this issue within Islamic boarding schools (pesantren) remains severely limited. This community service project aims to enhance mental health awareness and literacy among students (santri) at Sirojul Ulum As-Sarqowi Pesantren in Gondanglegi, Malang. The intervention method was executed in three primary stages: preparation, implementation of social advocacy utilizing interactive lectures and the "Botak-Batuk-Batik" educational game, and evaluation. The program engaged 40 participants, including junior and senior high school-aged santri and school administrators, in collaboration with the Youth Counseling and Information Center (PIKR) of Universitas Al-Qolam. The results demonstrate that integrating interactive lectures with educational games effectively mitigated boredom while facilitating the students' understanding of stress management and identification of mental health disorders. In conclusion, this interactive approach successfully fostered initial mental health awareness among students and established a foundation for sustainable collaboration between the pesantren and external youth empowerment organizations to optimize the students' learning process.